Chemoradiation-induced pneumonitis in patients with unresectable stage III non-small cell lung cancer: A systematic literature review and meta-analysis. (December 2022) - Kuang, Yuting; Pierce, Christine M.; Chang, Hsiu-Ching; Sosinsky, Alexandra Z.; Deitz, Anne C.; Keller, Steven M.; Samkari, Ayman; Uyei, Jennifer
Highlights: The risk of radiation pneumonitis (RP) in concomitant immunotherapy use is unclear. A systematic literature review with Bayesian meta -analysis was performed. There is a risk of pneumonitis in stage III NSCLC receiving chemoradiation. Pooled incidence of grade 3–5 RP was 3.62% (RCT) and 5.98% (observational study). Baseline risk of RP helps to inform the safety of concomitant immunotherapy use. Abstract: Introduction: High-grade pneumonitis is a severe and potentially life-threatening adverse event associated with concurrent chemoradiation (cCRT) in patients with non-small cell lung cancer (NSCLC). The aim of this study was to summarize and quantify the incidence of severe (grade 3–5) cCRT-induced pneumonitis in unresectable stage III NSCLC patients. Methods: A systematic literature review and meta -analysis were performed in accordance with PRISMA guidelines. Published literature was searched for randomized controlled trials (RCTs), observational studies, and non-randomized trials from 2014 to April 2020. The primary outcome of interest was incidence of grade 3–5 pneumonitis. Results: Included were 17 studies for the review and 11 for the meta -analysis (1, 788 participants); all studies examined radiation-related pneumonitis (RP). The pooled incidence of cCRT-induced grade 3–5 RP in unresectable stage III NSCLC patients was estimated to be 3.62% [95% confidence interval (CI): 1.65–6.21] in RCTs, 5.98% [95% CI: 2.26–12.91] in observational studies, and 7.85% [95% CI: 4.08–13.10] in observational studies using platinum-based doublet chemotherapies. Conclusion: These results suggest the incidence of severe and fatal RP in patients with unresectable stage III NSCLC treated with cCRT ranges from 3.62% to 7.85%, with incidence varying by study design and chemotherapy regimen. Estimates of RP incidence were higher in the real-world setting compared to RCTs. These results can be used to contextualize the baseline risk of cCRT-induced pneumonitis in unresectable stage III NSCLC to better understand the adverse event of pneumonitis associated with novel immunotherapy treatments indicated for concomitant use with this modality.